Facility Variation and Predictors of Do Not Resuscitate Orders of Hemodialysis Patients in Canada: DOPPS - Danielle Moorman; Ranjeeta Mallick; Emily Rhodes; Brian Bieber; Gihad Nesrallah; Jan Davis; Rita Suri; Jeffery Perl; Peter Tanuseputro; Ronald Pisoni; Bruce Robinson; Manish M. Sood (Canadian Journal of Kidney Health and Disease, 2019)
Background: Life expectancy in patients with end-stage kidney disease treated with hemodialysis (HD) is limited, and as such, the presence of an advanced care directive (ACD) may improve the quality of death as experienced for patients and families. Strategies to discuss and implement ACDs are limited with little being known about the status of Do Not Resuscitate (DNR) orders in the Canadian HD population. Objectives: Using data from the Dialysis Outcomes and Practice Patterns Study (DOPPS), we set out to (1) examine the variability in DNR orders across Canada and its largest province, Ontario and (2) identify clinical and functional status measures associated with a DNR order. Design: We conducted a retrospective cohort study using data from the DOPPS Canada Phase 4 to 6 from 2009 to 2017. Setting: DOPPS facilities in Canada. Patients: All adults (>18 years) who initiated chronic HD with a documented ACD were included. Measurements: ACD and DNR orders. Methods: Descriptive statistics were compared for baseline characteristics (demographics, comorbidities, medications, facility characteristics, and patient functional status) and DNR status. The crude proportion of patients per facility with a DNR order was calculated across Canada and Ontario. Functional status was determined by activities of daily living and components of the Kidney Disease Quality of Life (KDQOL)-validated questionnaire. We used generalized estimating equations (GEEs) to create sequential multivariable models (demographics, comorbidities, and functional status) of variables associated with DNR status. Results: A total of 1556 (96% of total) patients treated with HD had a documented ACD and were included. A total of 10% of patients had a DNR order. The crude variation of DNR status differed considerably across facilities within Canada, between Ontario and non-Ontario, and within Ontario (interprovince variation = 6.3%-17.1%, Ontario vs non-Ontario = 8.2% vs 11.7%, intraprovincial variation [Ontario] = 1%-26%). Patients with a DNR order were more commonly older, white, with cardiac comorbidities, with less or shorter predialysis care compared with those without a DNR order. Patients with a DNR order reported lower energy, more difficulty with transfers, meal preparation, household tasks, and financial management. In a multivariate model, age, cardiac disease, stroke, dialysis duration, and intradialytic weight gain were associated with DNR status. Limitations: Relatively small number of events or measures in certain categories. Conclusions: A large inter- and intraprovincial (Ontario) variation was observed regarding DNR orders across Canada highlighting areas for potential quality improvement. While functional status did not appear to have a bearing on the presence of a DNR order, the presence of various comorbidities was associated with the presence of a DNR order.